2002
DOI: 10.1023/a:1020392309715
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Considering recent findings that cyclooxygensase-2 (COX-2) is involved in the progression of colorectal carcinoma (CRC), the role of COX-2 in promoting invasion and angiogenesis was investigated by evaluating the relationship of COX-2 expression to various clinicopathological variables, including plasminogen activating system (PA system) and vascular endothelial growth factor (VEGF). Tumor tissues from 71 patients with CRC were assayed to determine the antigen levels of urokinase-type plasminogen activator (uP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…In agreement with other studies, p53 overexpression was found in 50.3% (81/161) of the colorectal cancers. Many other studies have demonstrated that p53 overexpression in colorectal cancer was closely related to clinicopathologic parameters and prognosis 12,19. In our study, p53 overexpression was correlated with age and depth of tumor invasion.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In agreement with other studies, p53 overexpression was found in 50.3% (81/161) of the colorectal cancers. Many other studies have demonstrated that p53 overexpression in colorectal cancer was closely related to clinicopathologic parameters and prognosis 12,19. In our study, p53 overexpression was correlated with age and depth of tumor invasion.…”
Section: Discussionsupporting
confidence: 75%
“…In our study, the expression rate of COX-2 was found to be 47.8% by immunohistochemical analysis, a result slightly lower than that found in other studies. However, other studies have reported that overexpression of COX-2 protein has been found in 21% to 25% of colorectal cancers 12-14. The discrepancies in the positive rate of COX-2 protein expression among the different studies may be explained by several factors, including variability in population size and characteristics, antibodies, lack of standardization in testing methods, and especially the differences in the choice of the scoring system or cutoff levels.…”
Section: Discussionmentioning
confidence: 96%
“…1 ). Eight retrospective observational studies were included in this meta-analysis involving 937 patients [ [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ], their baseline characteristics and quality assessments are shown in Table 2 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Elevated COX-2 expression has been associated with poor prognoses in lung [40–42] and other cancers, such breast [43], head and neck [44], colon [45], and cervix carcinomas [46]. However, little is known about COX-2 single nucleotide polymorphisms in NSCLC.…”
Section: Discussionmentioning
confidence: 99%